Non-Classical Approach to a History of Philosophy: Modern Status and Research Prospects - Vadym Tytarenko (International Society of Philosophy and Cosmology, 2019)
The paper touches upon some issues on the present condition and prospects of the research methodology in the field of history of philosophy. The author claims that modern Ukrainian history of philosophy is mostly grounded on the principles of a classical theoretical approach which date back to the philosophical traditions of Hegelianism and Marxism. The classical approach is determined by a specific theory of the hitorico-philosophical process in which it appears as a particular linear set of events objectively connected and influencing each other. Such theory presupposes a certain set of methods and rules of their application. This peculiarity makes the system isolated from the others and provides limitations that influence the effectiveness of the research. The author asserts that to optimize the effectiveness and increase the heuristic potential of the research in the field of history of philosophy the classical methodological approach should be gradually replaced by the non-classical. The main properties of the non-classical approach are openness, methodological communication with the other research fields, equal evaluation of the importance of various philosophical notions, personalities and events. Author, generalizing the modern research experience in the field of methodology of history of philosophy, suggests several strategies for improvement and transformation of the existing research methodology and the development of a non-classical approach to the history of philosophy.